A little help from steroids in oncology - Lossignol, Dominique (J Transl Int Med, 2016)
Steroids are widely used in oncology and have been demonstrated to possess an anticancer effect or antiswelling effect. They are considered to improve refractory symptoms such as dyspnea or gastrointestinal (GI) obstruction. However, their roles in nonspecific indications are not well proved. Clinical practice and several studies suggest that corticosteroids may be effective in the treatment of bone and neuropathic pain, when administered along with opioids and with other adjuvant analgesics. The decrease in pain intensity is probably connected with both anti-inflammatory and antiswelling effects as well as modulation of neuroimmune interactions and an inhibition of angiogenesis.